Environmental Regulation Investment Protection and 'Regulatory Taking' in international law - Kolo, Abba (2001)
THIS article addresses a currently very controversial issue—the question of environmental regulation of foreign investment and the limits on such national regulation by international law, in particular by recently completed and nego-tiated multilateral investment Treaties (MITs). It contributes to the emerging discussion on how and where to draw the line between legitimate non-compensable national regulation aimed at protecting the environment, or `human, animal or plant life or health'l on one hand, and regulation which is `tantamount' to expropriation requiring compensation, on the other. It is a question that is largely responsible for the 1998 collapse of the negotiations for a Multilateral Agreement on Investment (MAI) within the OECD.2 This experience is currently the main obstacle for negotiating multilateral invest-ment agreements—and it has already become a problem for the proper imple-mentation of the already existing ones—in particular the novel and far-reaching investor-state arbitration under Chapter XI of NAFTA and Art.